STUDY OF THE DEMAND FOR SOFTWARE DEVELOPMENT TECHNOLOGIES IN LATVIA - Fadejevs, Aleksandrs; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
This article focuses on software development technologies used by companies operating in Latvia in 2021. The aim of this work is to determine which software development technologies are most frequently used in Latvia this year. Determine what types of technologies they relate to, and finally draw appropriate conclusions.